2019
DOI: 10.1111/cch.12663
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal validation of the Caregiver Priorities and Child Health Index of Life with Disabilities in a Dutch sample of nonambulatory children with severe disabilities

Abstract: Background: The purpose of this study was to evaluate the longitudinal validity of the Dutch version of the Caregiver Priorities and Child Health Index of Life with Disabilities (CPCHILD), a health-related quality of life instrument for nonambulatory children with severe motor disabilities and accompanying disorders. Methods: The effect of two interventions, Botox injections in the hip region and percutaneous endoscopic gastrostomy, was followed over time. Caregivers (n = 38) of nonambulatory children (26 boys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The underrepresentation of men (fathers and male DSPs) might have influenced the results, given that the views of the caregivers were incorporated in completing the proxy-measure. As indicated by previous studies (Narayanan et al, 2006;Zalmstra et al, 2015Zalmstra et al, , 2019, however, mothers are more likely to participate. It is also known that the majority of DSPs are women.…”
Section: Methodological Reflections and Further Researchmentioning
confidence: 72%
“…The underrepresentation of men (fathers and male DSPs) might have influenced the results, given that the views of the caregivers were incorporated in completing the proxy-measure. As indicated by previous studies (Narayanan et al, 2006;Zalmstra et al, 2015Zalmstra et al, , 2019, however, mothers are more likely to participate. It is also known that the majority of DSPs are women.…”
Section: Methodological Reflections and Further Researchmentioning
confidence: 72%
“…The GMFCS classifies motor function in CP, ranging from level I (independent walking) to level V (children are dependent on wheeled mobility and have limited head and trunk control). The CPCHILD has shown to be one of the strongest outcome measures with the strongest psychometric properties and clinical utility for children with CP [ 17 , 18 ]. The CPCHILD questionnaire gathers information pertaining to the previous two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…One study (high risk of bias) conducted a cost‐effectiveness analysis comparing standard‐of‐care standing with the Innowalk and concluded that although societal and health care costs were greater for the Innowalk, benefits were also greater 52 . However, the reported increase in health‐related quality of life was still less than the minimal clinically important difference 90 and may be within measurement error 91 . No other studies exploring costs or cost‐effectiveness were identified.…”
Section: Resultsmentioning
confidence: 99%